Early-Years Prospective Teachers' Definitions, Examples and Non-examples of Cylinder and Prism - Ulusoy, Fadime (University of Plymouth, 2019)
This study investigates early-years prospective teachers' definitions, examples, and non-examples of cylinder and prism. The data were collected from 72 early-years prospective teachers via written tasks and classroom discussions. In written tasks, they were requested to define and then to give different examples and non-examples of cylinder and prism. The results indicated that prospective teachers defined cylinder based on prototypical cylinder with circle bases without mentioning all critical attributes of cylinder. They mostly provided correct examples and non-examples for cylinder. They did not pay attention critical and non-critical attributes of prism. Some prospective teachers drew cone and pyramids as the examples of prism. Their daily-life examples had similarity with the examples presented in textbooks and other curriculum materials. This study revealed that there is relationship between prospective teachers' definitions, daily-life examples, drawings, and non-examples. Possible reasons for these results are discussed and elaborated.
Keywords: 4. Education